تقدير دالة الطلب على النقود للسودان في الفترة 1960-2014 - محمد، صلاح الدين محمد حامد (جامعة البحر الأحمر, 2016)
This study aimed to estimate the demand for money of the Sudanese economy using annual time series data covering a period of fifty five years extending from 1960 to 2014 by the use of an empirical methodology based on augmented Dickey – Fuller and Phillips Perronunit root tests and Johansen co integration test, Ordinary Least Squares Estimates (OLS), and Vector Error Correction Model (VECM). The tests revealed that all variables of the study are stationary in level and revealed a long run equilibrium relationship between the demand for money and it’s determinants and also revealed the inelasticity of the demand for money and the negative effect of inflation rate and foreign exchange rate on the demand for money of the Sudanese economy during the period of the study. The study recommended the importance of concentrating on the demand for money (narrow money) to achieve stability in the domestic price level and stability of the foreign exchange rate by keeping money supply at levels that accelerate economic growth and at the same time don’t cause an increase in inflation rates.
هدفت هذه الدراسة إلى تقدير دالة الطلب على النقود للاقتصاد السودانيمستعينة ببيانات سلاسل زمنية سنوية تغطي فترة تمتد لخمسة و خمسين عاما تمتد من 1960 و حتى 2014 بإستخدام منهج تجريبي يقوم على الاستعانة باختباري ديكي فولر المعدل Fuller-Augmented Dickey وفيليبس بيرون Perron-Phillips لجذر الوحدة Unit Root اختبار جوهانسن للتكامل المشتركJohansen Cointegration Test تقديرات المربعات الصغرى العادية Ordinary Least Squares Estimates ، وأخيرا نموذج متجه تصحيح الخطأ Vector Error Correction Model، و أظهرت نتائج الاختبارات أن جميع متغيرات الدراسة ساكنة في المستوى Stationary in level. أظهرت وجود علاقة توازنية طويلة الأجل بين الطلب على النقود ومحدداته وأظهرت كذلك عدم مرونة الطلب على النقود والإثر السلبي لكل من التضخم وسعر الصرف على الطلب على النقود الاقتصادي للسودان خلال فترة الدراسة. أوصت الدراسة بأهمية التركيز على الطلب على النقود بمعناه الضيق M1 لتحقيق استقرار مستوي الأسعار المحلية واستقرار سعر الصرف الأجنبي وذلك بالإبقاء على عرض عند مستويات تسهم في تسريع نمو الاقتصاد ولا تتسبب في نفس الوقت في زيادة معدلات التضخم.
Keywords: الطلب على النقود -- الناتج المحلي الإجمالي الحقيقي -- التضخم -- سعر الصرف -- الرسائل الإعلامية -- السودان